Repair of Ventral Hernia by a Simplified Procedure - Singh, Dr. Joginder; Bhardwaj, Dr. D. N.; Singh, Dr. Bholla (Indian Journal of Plastic Surgery, 1972)
1) Fifty cases of ventral hernia, treated by simplified interrupted inverting suture method using cotton suture material, are reported.2) Opening the hernia sac for adhesions, limited dissection of sheath, wide wound debridement and no provision of any drainage form main features of the procedure.3) Haematoma, scroma and wound inifection are eliminated, though serum discharge through superficial wound gaping occurred in 8 percent cases of big hernia. Post-operative stay is minimal and no recurrence occurred on follow up.